EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DENGAN PENDEKATAN OPEN-ENDED PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI DISPOSISI MATEMATIS SISWA KELAS VIII SMP NEGERI DI KABUPATEN PURWOREJO - Wijayaanto, Zainnur; Budiyono, Budiyono; Sujadi, Imam (Jurnal Pembelajaran Matematika, 2014)
Abstract: The study aimed to know: 1) which one of the learning models gave a better achievement between Think Pair Share (TPS) cooperative learning model with Open-Ended Approach, TPS, or direct learning model, 2) which one of the students with mathematical disposition category had a better achievement between students with high, moderate or low mathematical disposition, 3) in each studentâs mathematical disposition category, which learning model gave a better studentâs achievement in mathematics, 4) in each learning models, which one of the students with mathematical disposition category had a better studentâs achievement in mathematics. This was quasi-experimental study with 3x3 factorial design. The study population was all eighth grade students of state junior high school in Purworejo District. Instruments used to collect data were mathematics achievement test and the studentâs mathematical disposition questionnaire. The data were analyzed using unbalanced two ways ANOVA. Based on the data analysis, it was concluded that: 1) TPS with Open-Ended Approach gave better achievement than TPS and direct learning model while TPS and direct learning model gave same achievement, 2) the students with high mathematical disposition had better achievement than the students with moderate and low mathematical disposition, and the students with moderate mathematical disposition had better achievement than the students with low mathematical disposition, 3) at all categories of studentsâ mathematical disposition, TPS with Open-Ended Approach, TPS, and direct learning model gave the same achievement, 4) in the TPS with Open-Ended Approach and TPS, the students with high mathematical disposition had better achievement than the students with moderate and low mathematical disposition, and the students with moderate mathematical disposition had better achievement than the students with low mathematical disposition. In the direct learning model, the students with high mathematical disposition had better achievement than the students with moderate and low mathematical disposition, while the students with moderate and low mathematical disposition had the same achievement.Keywords: Think Pair Share (TPS), Open-Ended Approach, Direct Instruction, Mathematical Disposition, Learning Achievement in Mathematics.